Legionella pneumophila: an intracellular pathogen of phagocytes - Roy, Craig (Henry Stewart Talks, 2009)
The legionella life cycle, Identification of the dot and icm genes, The dot and icm genes define a new type IV secretion system, Intracellular replication, Endocytic membrane transport, Transport of the Legionella-containing vacuole, Legionella replication, The dot/icm system modulates Arf and Rab1, Can we identify Legionella proteins that modulate Arf and Rab1 function?, Activation of Arf by Legionella, Can Legionella modulate the function of other host GTPases?, Identification of DrrA, LepB, Legionella: The greatest cell biologist on Earth